The biphasic dose effect of lychee (Litchi chinensis Sonn.) pulp phenolic extract on alcoholic liver disease in mice. Issue 1 (12th December 2016) - Xiao, Juan; Zhang, Ruifen; Huang, Fei; Liu, Lei; Deng, Yuanyuan; Wei, Zhencheng; Zhang, Yan; Liu, Dong; Zhang, Mingwei
Abstract : Lychee pulp phenolic extract (LPPE) has a biphasic dose response in ethanol-induced liver injury in mice. Abstract : Lychee ( Litchi chinensis Sonn.), a subtropical fruit grown widely in Southeast Asia, has been used as a traditional Chinese medicine for liver protection. Our previous study showed that phenolics from lychee pulp had hepatoprotective activity against restraint stress-induced liver injury. The present study investigated the protective effects of lychee pulp phenolic extract (LPPE) on ethanol-induced liver injury and the mechanism responsible for these effects. Mice were divided into four groups and subjected to either a control liquid diet (control group, CON), a 4% (w/v) ethanol-containing liquid diet (ethanol group, EtOH), a 4% (w/v) ethanol-containing liquid diet supplemented with 0.4 g L −1 LPPE (low dose LPPE-supplemented group, EtOH + L-LPPE), or a 4% (w/v) ethanol-containing liquid diet supplemented with 0.8 g L −1 LPPE (high dose LPPE-supplemented group, EtOH + H-LPPE) for 8 weeks. The ethanol-induced hepatic steatosis and increases of triglyceride levels in the serum and liver were ameliorated by L-LPPE supplementation but aggravated by H-LPPE supplementation. Moreover, L-LPPE supplementation improved the antioxidant status, reduced the nuclear translocation of nuclear erythroid 2-related factor 2 (Nrf2), and reduced the expression of Nrf2 target genes in the liver. H-LPPE supplementation resulted in the improved antioxidant status and reduced the expression of Nrf2 target genes. Furthermore, L-LPPE suppressed the expression of lipid synthesis genes and increased the expression of fatty acid β-oxidation genes. However, H-LPPE increased the expression of genes responsible for lipid synthesis and uptake and reduced the expression of fatty acid β-oxidation genes. Additionally, L-LPPE supplementation effectively decreased the serum endotoxin level and reversed ethanol-induced alterations in the intestinal microbiota composition. Collectively, LPPE showed biphasic effects on ethanol-induced liver injury in mice, indicating that a moderate intake of LPPE or Litchi pulp could be useful for the prevention and control of alcoholic liver disease.